2018
DOI: 10.3889/oamjms.2018.090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Combined Use of Temocillin Disk and Mastdisks Inhibitor Combination Set Against Polymerase Chain Reaction for Detection of Carbapenem-Resistant Enterobacteriaceae

Abstract: AIM:To evaluate the diagnostic performance of MDI and temocillin disk (30 μg) for detection of carbapenem-resistant Enterobacteriaceae in comparison to real-time PCR.MATERIAL AND METHODS:Fifty specimens submitted to the Microbiology Laboratory of Ain Shams University Hospitals and showed resistance to carbapenem drugs through routine culture and susceptibility testing, were assessed by both temocillin disk (30 μg) and MDI set to detect carbapenem-resistant Enterobacteriaceae. Results were compared to real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…When they assessed for diagnostic accuracy, they reported a very low PPV (%27.6) with high NPV (%99.5) for diagnostic capability. Another study, by Shaker et al revealed in 48 OXA-48-positive CPE isolates that 30 µg temocillin disc had 97.9% sensitivity, 50% specificity, 97.95% PPV and 50% NPV for detecting OXA-48 production [18]. We demonstrated that temocillin disk diffusion method had a sensitivity of 100% and a specificity of 77.8% in detecting the presence of OXA-48.…”
Section: Discussionsupporting
confidence: 46%
“…When they assessed for diagnostic accuracy, they reported a very low PPV (%27.6) with high NPV (%99.5) for diagnostic capability. Another study, by Shaker et al revealed in 48 OXA-48-positive CPE isolates that 30 µg temocillin disc had 97.9% sensitivity, 50% specificity, 97.95% PPV and 50% NPV for detecting OXA-48 production [18]. We demonstrated that temocillin disk diffusion method had a sensitivity of 100% and a specificity of 77.8% in detecting the presence of OXA-48.…”
Section: Discussionsupporting
confidence: 46%
“…This problem is one of the main reasons for the expression of carbapenemase genes among members of this family [ 7 ]. Carbapenemase enzymes are the most common mechanism by which resistance to carbapenems arises [ 8 , 9 ]. Carbapenem resistance has been labelled in Enterobacteriaceae , mostly in Klebsiella pneumoniae compared to Escherichia coli or other Enterobacterial species, and in non-fermentative Gram-negative bacilli such as Pseudomonas aeruginosa and Acinetobacter baumannii [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, carbapenemases were chromosomally mediated in a few specific species, but now they mediate a plasmid, or both a chromosomal and a plasmid. This results in a more violent spread of resistance due to horizontal transfer between different bacterial species and genera [ 9 ]. Since 1993, different types of carbapenemases have been recognised belonging to three molecular classes, the Ambler classes A, B and D beta-lactamases [ 14 ]: class A carbapenemases, Klebsiella pneumoniae carbapenemase (KPC) enzymes; class B metallo-beta-lactamases (MBLs) such as New Delhi metallo-beta-lactamases (NDM), Verona integron-encoded metallo-beta-lactamase (VIM) and imipenemase (IMP) type enzymes; and class D carbapenem-hydrolysing oxacillinase (OXA) such as OXA-48 enzymes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the protocol, the boronic acid combined-disk tests using meropenem (10 μg) as the antibiotic substrate and 3-aminophenylboronic acid (3-APBA) (300 g, Sigma-Aldrich) as the inhibitor of KPC production was used. The detection of OXA-48 was performed in line with the EUCAST guidelines ( Shaker et al 2018 ). MDR and XDR were defined according to a standardized international document ( Magiorakos et al 2012 ).…”
Section: Methodsmentioning
confidence: 99%